The Designation of Money as Evidence in Corruption Cases: A Legal Normative Study of Law Enforcement Practices in Indonesia - Durahman, Dani; Sihombing, Indra Gatot; Azhari, Arie; Setia Gunawan, Dini Eka; P Bunga, Dinda; Farida, Ade (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Corruption offences in Indonesia not only cause financial losses to the state, but also undermine public trust in the legal system. In the law enforcement process, money obtained through corruption is often used as key evidence to uncover the flow of funds and prove the element of state losses. This study aims to analyse the designation of money as evidence in corruption cases through a normative legal approach by examining legislation, legal doctrine, and judicial practice in Indonesia. The results of the study show that the determination of money as evidence has a strategic role in proving the elements of unlawful acts and strengthening the construction of the public prosecutor's indictment. However, there are still problems related to seizure procedures, evidence management, and the return of state losses that are not yet optimal. The lack of synchronisation between the provisions in the Criminal Procedure Code, the Corruption Eradication Law, and practices in the field also hinders the effectiveness of law enforcement. Therefore, regulatory harmonisation and increased professionalism among law enforcement officials are needed so that the management of money as evidence can provide legal certainty, justice, and benefits in the eradication of corruption in Indonesia.